Hospice Care - Suzanna Smith (EDIS)
“Recently a friend’s mother, Alice, was diagnosed with lung cancer, and even though she received all the possible treatments, the cancer was incurable. She went into hospice care so that she could get professional help in preparing herself and her family for her death.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, August 2012.